Genome analysis of adenovirus type 3 isolated in Japan. - Shiao, S (1996)
Adenovirus type 3 (Ad3) isolates, isolated from 45 patients with acute conjunctivitis during the year 1990 in Japan, were studied by DNA restriction enzyme analysis with restriction endonucleases recognizing 6-bp sequences (BamHI, SmaI, HindIII, BglII) and endonucleases recognizing 5- or 4-bp sequences (HinfI and TaqI). All 45 isolates of Ad3 were identified as the genome type Ad3f by six endonucleases. They were further classified into three varieties by HinfI, varieties H1 (87.5%), H2 (8.9%), and H3 (2.2%), and into five varieties by TaqI, varieties T1 (75.6%), T2 (13.3%), T3 (2.2%), T4 (4.5%), and T5 (8.9%). The use of HinfI and TaqI was sufficient to distinguish six subgenome types: types Ad3fH1T1, Ad3fH1T2, Ad3fH1T4, Ad3fH1T5, Ad3fH2T1, and Ad3fH3T3. Among them, Ad3fH1T1 was predominant in areas where the virus is epidemic. The study showed that the same Ad3 genome type, genome type Ad3f, caused acute viral conjunctivitis even in different areas in Japan. The source and the route of infection were suggested to be common in areas where the virus is epidemic.